Life’s essential 8 and mortality in US adults with metabolic dysfunction-associated steatotic liver disease - Yingying Zhang; Pingping Wang; Fan Tu; Hao Kang; Chengfeng Fu (BMC Public Health)
Abstract Background Metabolic dysfunction-associated steatotic liver disease (MASLD) is linked to increased all-cause mortality due to metabolic dysfunctions like obesity, diabetes, and cardiovascular diseases. This study examines the association between Life’s Essential 8 (LE8) scores and both all-cause and cardiovascular disease (CVD) mortality in MASLD participants. Methods Data from 5,916 MASLD participants in the NHANES (2005–2018) were analyzed. Associations between LE8 scores and all-cause and CVD mortality were assessed using Cox proportional hazards models, with follow-up until December 31, 2019. Dose-response relationships and survival differences were evaluated using Kaplan-Meier survival curves and Restricted Cubic Spline models. Results Over a median follow-up of 7.6 years, moderate and high LE8 scores were associated with 33% (HR: 0.67; 95% CI: 0.56–0.79) and 47% (HR: 0.53; 95% CI: 0.33–0.84) lower risk of all-cause mortality, respectively, compared to low scores. For CVD mortality, the adjusted HRs were 0.56 (95% CI: 0.41–0.78) and 0.35 (95% CI: 0.12-1.0). Higher LE8 scores were significantly associated with reduced cumulative incidence of all-cause and CVD mortality (log-rank P < 0.001). A 10-point increase in health behavior scores, particularly in diet, physical activity, and nicotine exposure, was linked to an 11% reduction in all-cause mortality risk and an 11% reduction in CVD mortality risk. Among health factors, only blood glucose showed a significant association with CVD mortality. Conclusion Higher LE8 scores in MASLD patients are associated with lower mortality risk, suggesting the potential value of promoting cardiovascular health in this population. Further research is needed to confirm these associations. Graphical Abstract